The impact of antigenic molecular mimicry on anti-cancer T-cell immune response - Tagliamonte, Maria; Buonaguro, Luigi (Frontiers in Oncology, 2022)
Individuals are exposed to intracellular pathogens (i.e. viruses and intracellular bacteria) and intestinal microbiota, collectively microorganisms (MOs), which enter the body during the host’s lifetime. Altogether, MOs are a natural source of non-self antigens (MoAs) expressed by host’s cells in the context of the HLA class I molecules, inducing a wide pool of specific memory CD8+ T cell clones. Such MoAs have been shown in selected cases to share sequence and structural homology with cellular self-antigens (molecular mimicry), possibly inducing autoimmune reactions leading to autoimmune diseases (ADs). We have recently shown that a molecular mimicry may be found also to self-antigens presented by cancer cells (i.e. tumor-associated antigens, TAAs). Consequently, memory CD8+ T cell clones specific for the MoAs may turn out to be a natural “anti-cancer vaccination” if a nascent tumor lesion should express TAAs similar or identical to MoAs. We postulate that selecting MoAs with high homology to TAAs would greatly improve the efficacy of cancer vaccines in both preventive and therapeutic settings. Indeed, non-self MoAs are potently immunogenic because not affected by central immune tolerance. Unravelling the impact of the antigenic molecular mimicry between MoAs and TAAs might pave the way for novel anti-cancer immunotherapies with unprecedented efficacy.